High performance N-doped moCNTs catalyst with graphene-like nanosheets structure for oxygen reduction. (25th May 2017) - Yu, Shuping; Chi, Xiangfang; Fan, Jianhua; Liang, Xinkai; Yang, Wensheng; Wang, Zhongming; Han, Kefei; Zhu, Hong
Abstract: N-doped mildly oxidized CNTs (moCNTs) catalysts for oxygen reduction reaction in proton exchange membrane fuel cells were prepared by a two-step method consisting of polymerization and pyrolyzation. The morphology of the electrocatalyst samples were characterized by scanning electron microscopy (SEM), high resolution transmission electron microscopy (TEM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). It was discovered that the N-doped moCNTs catalyst showed a graphene-like nanosheets nanostructure; electrocatalytic properties of the catalysts were investigated by cyclic voltammetry (CV), linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS). The experimental results exhibited remarkable catalytic activity in an acidic medium, with the onset potential, half-wave potential, and limiting current density reaching 0.87 V, 0.75 V (vs. reversible hydrogen electrode), and 3.5 mA/cm 2, respectively. It can be concluded that the high catalytic performance is due to the high content of graphitic nitrogen and the graphene-like nanosheets structure. Graphical abstract: Highlights: N-doped moCNTs nanosheet structure loading electrocatalysts were synthesized. They were synthesized by a chemical redox polymerization method, and low in cost. The catalysts showed excellent activity toward oxygen reduction in an acidic medium.